Homicide by Hanging: a Comprehensive Review of Published Literature - Safitry, Oktavinda; Putra, Afid Brilliana; Gustinanda, Jatmiko; Rakasiwi, Muhammad Ilham Dhiya (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2023)
Homicide by hanging is a rare incident and, in contrast to suicidal hanging cases, only limited number of homicidal hanging cases have been reported. This comprehensive review is conducted to summarize the published forensic pathology evidence in homicide by hanging. A systematic search in five journal databases resulted in 12 case reports. All articles passed the selection criteria and were appraised using JBI critical appraisal worksheet for case reports. Fourteen victims were reported which in most of the cases psychosocial background were reported. Household conflict was the common background. Reef knot was the majority knot being used. The autopsy findings vary in the studies, some of which reported intact larynx, thyroid, and hyoid cartilage. Only one case mentioned thyroid cartilage fracture. In addition to the ligature mark, other violence findings include bruises, abrasions, stab wounds, and sexual violence. Toxicological analysis was limited, only 3 case reports reported alcohol in the victim’s serum. There are no distinguishing features in the external or internal neck injuries attributable to homicidal hanging. A thorough autopsy and holistic approach should be considered. They are including demographic characteristics, location of the victim, social and psychiatric history, ligature’s characteristic, signs of violence and toxicological analysis.